Interrelation Between Conceptual and Linguistic Worldviews (Based on the Economic Lexical Item ‘CLIENT’) - Lesia Kushmar (Психолінгвістика)
This article presents a theoretical approach to the concept interpretation “worldview” which expresses human knowledge about environment. The difference between conceptual and linguistic worldviews has been determined. Associative meaning represents the conceptual worldview. Vocabulary definitions reflect the linguistic worldview. To identify main peculiarities in conceptual and linguistic worldviews the lexical item ‘CLIENT’ was selected according to criteria: contextual conditioning, frequency, information, presence in dictionaries and encyclopedias of different areas, expressing relevant concepts nowadays. 915 respondents took part in the experiment. Obtained results (1,600 reactions) have been processed using statistical methods. The application of modeling allowed creating the associative field structure defining core and periphery. Items representing essential features of the concept form the core; secondary features of the subject form the periphery. The core and periphery combine associative meaning of the item. Comparison of lexical and associative meanings has been made according to algorithm: defining main components in the lexeme structure using structural-semantic principle; calculation of core reactions because the lexicon core of the native speaker reflects the actual worldview; establishment total number of core reactions that are connected with vocabulary; determination the level of lexical and associative meanings’ approximation. The economic lexical item ‘CLIENT’ is on the edge of incomplete coincidence according to association and lexical meanings. This fact allows arguing that the conceptual worldview is more dynamic than linguistic. Changes in reality are reflected in core reactions of the associative field only with time being reflected in the lexical meaning.